Penerapan Media Pembelajaran Pohon Cermat Literasi Untuk Meningkatkan Keterampilan Menganalisis Unsur Intrinsik Teks Cerpen Kelas XI-D2 SMA Negeri 9 Surabaya - Nindita Novi Permatasari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Based on observations in classes XI-D2 of SMA Negeri 9 Surabaya, researchers found that there was a problem in learning, namely the lack of teacher skills in creating an effective learning atmosphere. This condition is the cause of students not being very active in learning, so that the achievement of their learning outcomes in the competence of analyzing the intrinsic elements of short story builders is not good. The focus of this study is to evaluate the effectiveness of the application of the "Literacy Tree" learning media as an effort to improve the skills of analyzing the intrinsic elements of short story builders. The research method applied is classroom action research. The technique used in this study is qualitative descriptive data analysis. This research was carried out in three stages, including, the pre-cycle stage, cycle one, and cycle two. The results of the study show that the activeness and learning outcomes of students have increased which occurs in the stages of cycle one and cycle two.